An analysis of the accuracy of selected indicators for sustainability assessment of energy savings performance projects supporting the life cycle analysis - Aldona Kluczek (Economic and Environmental Studies (E&ES), 2018)
More and more energy projects expect to improve their operating energy efficiency performance by applying a set of energy performance indicators supporting the life cycle analysis to make energy saving plans and to provide decision makers with the methods to analyse accuracy of the applied indicators. Energy savings are crucial from the environmental point of view to reduce the resources and the cost of energy conversion, distribution and use, resulting in high-energy intensities. The purpose of the paper is to analyse the accuracy of selected indicators for energy-efficient performance projects supporting the life cycle analysis. Primary, the analytical hierarchy process method is used to determine relevant indicators being representatives of the whole picture of industrial energy projects. The indicators characterize the impacts of energy-related production operations on the energy efficient performance of industrial plants or energy projects residing in the three sustainability aspects: the environment, the economy and the social capital. Then, a multiple regression is used to analyse the accuracy of selected indicators to be evaluated in energy projects. The results of the analysis are selected LCA-based energy-related indicators representing sustainability assessment of energy savings performance projects. These variables can be attributed to energy-efficient improvements for assessing the sustainability and making simple comparisons through analysing the values of particular indicators.
Keywords: C10; Q40; 330; sustainability assessment; AHP; multiple regression; energy projects; life cycle analysis